Prevalence of endoscopic improvement and endoscopic remission according to patient reported outcomes in ulcerative colitis - Dulai, Parambir S. (Aliment Pharmacol Ther, 2019)
BACKGROUND: We quantified the prevalence of endoscopic improvement and remission amongst ulcerative colitis patients with various permutations of patient reported outcomes. METHODS: Individual participant data from active intervention and placebo arms of clinical trials of infliximab, golimumab, vedolizumab, and tofacitinib were pooled to estimate the prevalence of endoscopic improvement (Mayo endoscopic sub-score [MES] 0 or 1) and remission (MES 0) scores with various permutations of the rectal bleeding sub-score (RBS) and stool frequency sub-score (SFS) of the Mayo score, following induction (6–8 weeks) and maintenance (30–54 weeks) therapy. Subgroup analyses were performed by year of publication and centrally read endoscopy scoring. RESULTS: Data from 2,586 trial participants were analyzed. Using locally scored endoscopy, the prevalence of endoscopic improvement and remission was highest among participants with a RBS 0 + SFS 0 post induction (MES 0/1: 81%, [95% CI 78–84]; MES 0: 29% [26–33]) and during maintenance (MES 0/1: 91% [87–93]; MES 0: 57% [52–62]). Prevalence estimates were lower for more recently performed trials (p<0.01). In comparison to locally scored endoscopy, when using central endoscopy scoring the prevalence of endoscopic improvement and remission were lower post-induction (MES 0/1 57% [50–64], p<0.001; MES 0 15% [11–21], p=0.09) and during maintenance (MES 0/1 74% [67–81], p=0.001; MES 0 31% [24–38], p=0.001) for participants achieving a RBS 0 + SFS 0. CONCLUSIONS: Approximately 8 out of 10 patients with normalization of rectal bleeding and stool frequency have improvement in endoscopic disease activity, whereas, approximately only half of these patients have endoscopic remission.